THE ACOUSTIC FEATURES OF EMPHATICITY IN INDONESIAN - Sugiyono, Sugiyono (Kajian Linguistik dan Sastra, 2009)
This study describes prosodic features which marked the emphatic meaning in Indonesian from Indonesian speaker whose mother tongue is, for instance, Javanese,Â Sundanese, Betawi, Bataknese, Bugisnese, Minangnese, Maâanyanese, Balinese, andÂ Mandailing. This study is conducted by applying experimental phonetic approach thatÂ is by selecting imperative sentences Tutup pintu! âClose the door!â as a target sentence.Â The data are collected by asking a subject to commend and to repeat the same command to a child or someone who is of the same age of his child to close the door. AllÂ collected data are measured in terms of its frequency, intensity, and duration. ThoseÂ three features are then analyzed statistically to find out the significance differences ofÂ acoustic feature difference on every level of utterance emphaticity. The results of thisÂ study shows that frequency, intensity, and duration are significant markers which differentiate emphaticity level. In terms of frequency, the higher the emphaticity level ofthe utterance is, the higher the frequency of the base pitch, final pitch, and pitch rangeÂ of that utterance will be. From the sound intensity point of view, the emphaticity ofÂ utterance is marked by base intensity and intensity range. The utterance with highÂ emphaticity level is marked by high base intensity and wider range intensity. FromÂ duration point of view, the utterance emphaticity is marked by the duration of all vowels. The height of emphaticity level is marked by the length of time needed by theÂ vowels to be uttered. The emphaticity markers show meaningful correlation.Keywords: acoustic phonetics; experimental phonetics; speech perception; andprosodie feature